Capital Flow Bonanzas as a Fundamental Ingredient in Spain's Financial Crises, 1850-2015 - Concha Betrán; María A. Pons (European Historical Economics Society (EHES), 2019)
Among the characteristics of Spanish financial crises over the last 165 years, we highlight their relatively high frequency and, since 1973, their severity (including 2008, the most severe crisis yet). By analysing monetary policy regimes, financial structure, and the main crisis determinants (factors associated with crises), as well as the resolution to the crises, we can conclude that capital flow bonanzas are a key factor in most financial crises; when a capital flow bonanza occurred, it increased both the probability of a subsequent crisis and its severity.
Keywords: N13; N14; O52; I30; 330; Spain; income per person; productivity; inequality; living standards